Strategy of Ciplukan Fruit Agribusiness Development (Physalis peruviana) At Waaida Farm, West Java - Muhammad Kemalvin Akbar Nugraha (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
Waaida Farm is a pioneer company of agribusiness of Physalis peruviana “ciplukan” in Indonesia. Waaida Farm started its cultivation of “ciplukan” with the considerations of “ciplukan” that has a big market opportunity. However, Waaida Farm could just fulfill the demand from Java so far because of its low production. The object of this research is to give a solution regarding the agribusiness developing strategy of “ciplukan” based on internal and external factors analysis which can be done at Waaida Farm. This research uses descriptive-qualitative design and study case research technique. Data collecting method used in this research is through interview and literature study. In needs to find the right developing strategy, there needs to be a matrix analysis of IFAS, EFAS, IE, SWOT and QSP. The SWOT analysis resulted five strategy formulations that can be implemented at Waaida Farm. The matrix QSP analysis resulted the right priority strategy for Waaida Farm, that is to invest the company’s profit for purchasing cooler boxes to overcome production shortages in certain periods and to increase the number of sales.